The implementation of Moodle platform through lecturer’s perspectives at English department - Tazkiyatunnafs Elhawwa (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2017)
Information and Communication Technology is now becoming an essential part of everyday life of most people in the world. This paper analysed the main functionalities and tools available in the Moodle platform and their use through lecturer’s perspectives at English Department of IAIN Palangka Raya. This study belongs to descriptive qualitative research. In the present study, teachers are expected to implement the Moodle platform of Information, Communication and Technology (ICT) in EFL classes, and make the Moodle platform of ICT becoming a complement to conventional teaching in EFL classrooms, especially when developing listening, reading and writing skills in English. The results showed that the Moodle platform contains some of the main tools of the standard Moodle platform like assignments, chats, forums, news and quiz/survey. The most the students purposes of the use of the Moodle platform were ‘download materials’, ‘news’ and ‘deliver assignments’, and the most used information materials are ‘texts’ and ‘slides’.